Predictors of post-traumatic growth in stroke survivors. Issue 24 (20th November 2018) - Kelly, Grace; Morris, Reg; Shetty, Hamsaraj
Abstract: Purpose: The development of post-traumatic growth was studied longitudinally within 14 months poststroke. The predictions of two models of post-traumatic growth were examined. Method: Forty-three stroke survivors were investigated at two time points (i.e., time 1 and time 2), six months apart. Each completed the Post-traumatic Growth Inventory, Rumination Scale, Impact of Events Scale, Multidimensional Scale of Social Support, the Barthel Index and the COPE scale. Results: Post-traumatic growth was evident four to five months after stroke, increasing significantly over the next six months at which point levels resembled those reported in cross-sectional stroke studies. Active and denial coping and rumination at time 1 were positively associated, and age was negatively associated, with post-traumatic growth at time 2, but acceptance coping was not associated. Neither active coping nor rumination mediated the effect of social support on post-traumatic growth as predicted. As predicted, rumination mediated the relationship between post-traumatic stress and post-traumatic growth. Exploratory stepwise regression demonstrated rumination and active coping at time 1 accounted for 45% of variance in post-traumatic growth at time 2. Conclusions: Post-traumatic growth can develop soon after stroke. Deliberate rumination is a key factor in post-traumatic growth. Both active coping and denial coping were associated with post-traumatic growth demonstrating the psychological complexity of poststroke adjustment. Implications for rehabilitation: Therapists can expect stroke survivors to show post-traumatic growth in the first months after stroke. Therapists should look to promote post-traumatic growth and positive adjustment through working with survivors to increase active coping (attempts to deal effectively with the impact of stroke) and rumination (cognitive processing of the impact of the stroke). Since denial coping was also associated with posttraumatic growth, stroke survivors who maintain overly optimistic views about the severity and impact of their stroke are likely to benefit from therapists continually facilitating capacity for growth and well-being.